Defying the Nazis : the Sharps' war [videorecording (DVD)] - Hanks, Tom; Goldman, Marina; Mirowitz, Sheldon; Shaffer, Deborah; Berz, Michael Julian (PBS Distribution, 2016)
Tells the never-before-told story of Waitstill and Martha Sharp, an American minister and his wife from Wellesley, Massachusetts, who left their children behind in the care of their parish and boldly committed to a life-threatening mission in Europe. Over two dangerous years they helped save scores of imperiled dissidents and refugees fleeing the Nazi occupation across Europe.